Alterations in some haematological parameters, ascorbic acid and pantothenic acid levels among pregnant women with plasmodium parasitaemia in Sokoto, Nigeria - Sulaiman Sule Umar , Osaro Erhabor , Yakubu Abdulrahaman , Isaac Zama , Festus Uchechukwu Onuigwe , 1 1 2 Hauwa Buhari, Aliyu Bagudo , Ahmed Marafa , Tosan Erhabor (Sokoto Journal of Medical Laboratory Science)
Malaria in pregnancy is a major contributor to adverse maternal and prenatal outcome. In hyper endemic areas like ours, it is a common cause of anaemia and the haematological abnormalities. This case-control study evaluated the full blood count, ascorbic acid and pantothenic acid level of sixty (60) malaria parasitized pregnant women. Participants were recruited from Antenatal Clinic of Specialist Hospital Sokoto. A structured interviewer-administered questionnaire was used to obtain some socio-demographic characteristic and blood samples were collected and examine for malaria parasite, some haematological parameters (HCT, HGB, WBC, RBC and platelet count) were measured using the HA6000 auto-haematology analyzer (Perlong Medical Equipment Company). Ascorbic acid levels were assayed by a standard chemical method and pantothenic acid levels was analyzed using the ID-VIT pantothenic acid ELISA kit. Malaria parasitaemia and parasite load was confirmed by the examination of a Giemsa- stained thin blood film. Data generated was analyzed using SPSS 22.0 statistical package. A p- value ≤ 0.05 was considered significant in all statistical comparisons. The HCT, HGB RBC and Platelet counts of the parasitized subjects were significantly lower compared with the controls (p<0.05). Also, the ascorbic acid level of parasitized subjects was significantly lower compared to that of controls. There was a strong correlation between ascorbic acid and platelet count (r= 0.413 and p= 0.00). The mean parasite count among the parasitized subjects was 5.93 ± 2.72 × 103/ìL. Findings of this study has shown that malaria in pregnancy causes decrease in vitamin C and some of the haematological parameters. There is need to routinely monitor the vitamin C and full blood count should among parasitized pregnant women. We advocate that vitamin C and pantothenic acid be included in the guidelines of multivitamin supplementation particularly among plasmodium parasitized pregnant women.